Repetitive Transcranial Magnetic Stimulation in Spinocerebellar Ataxia: A Pilot Randomized Controlled Trial - Manor, Brad; Greenstein, Patricia E.; Davila-Perez, Paula; Wakefield, Seth; Zhou, Junhong; Pascual-Leone, Alvaro (Frontiers in Neurology, 2019)
Spinocerebellar ataxia (SCA) is a neurodegenerative disorder caused by dysfunction of the cerebellum and its connected neural networks. There is currently no cure for SCA and symptomatic treatment remains limited. We here aim to examine the effects of a repetitive transcranial magnetic stimulation (rTMS) targeting the cerebellum on clinical impression, postural control and gait in patients with SCA. In this randomized, double blinded and sham control study, twenty individuals aged 18-75 years with SCA confirmed by genetic testing completed rTMS or sham intervention comprising 20 sessions of MRI-guided stimulation over the cerebellum. Baseline assessments included the Standard Ataxia Rating Assessment (SARA), the 9-hole peg test of manual dexterity, the Timed Up-and-Go (TUG) test, standing postural control with eyes-open and eyes-closed, and gait. Immediate (within one-week) and one-month follow-ups were completed. Intervention compliance was high (19±2 of 20 sessions) and no rTMS-related adverse events were reported. rTMS, compared to sham, was associated with greater percent improvement in SARA total score from baseline to the one-month follow-up (p=0.02). Secondary analyses of individual SARA items revealed that rTMS improved performance within the “stance” sub-score only (p=0.006). This functional change was accompanied by improvement to several objective metrics of postural sway during eyes-open and eyes-closed standing (p<0.01). rTMS did not influence the 9-hole peg test, TUG, or gait kinematics. A 20-session rTMS intervention is safe and feasible for those with SCA. Additional research is warranted to confirm the observed longer-term benefits of this intervention on standing postural control.